Drug Repurposing in Neurological Disorders: Implications for Neurotherapy in Traumatic Brain Injury. (December 2021) - Shakkour, Zaynab; Habashy, Karl John; Berro, Moussa; Takkoush, Samira; Abdelhady, Samar; Koleilat, Nadia; Eid, Ali H.; Zibara, Kazem; Obeid, Makram; Shear, Deborah; Mondello, Stefania; Wang, Kevin K.; et al.
Traumatic brain injury (TBI) remains a significant leading cause of death and disability among adults and children globally. To date, there are no Food and Drug Administration–approved drugs that can substantially attenuate the sequelae of TBI. The innumerable challenges faced by the conventional de novo discovery of new pharmacological agents led to the emergence of alternative paradigm, which is drug repurposing. Repurposing of existing drugs with well-characterized mechanisms of action and human safety profiles is believed to be a promising strategy for novel drug use. Compared to the conventional discovery pathways, drug repurposing is less costly, relatively rapid, and poses minimal risk of the adverse outcomes to study on participants. In recent years, drug repurposing has covered a wide range of neurodegenerative diseases and neurological disorders including brain injury. This review highlights the advances in drug repurposing and presents some of the promising candidate drugs for potential TBI treatment along with their possible mechanisms of neuroprotection. Edaravone, glyburide, ceftriaxone, levetiracetam, and progesterone have been selected due to their potential role as putative TBI neurotherapeutic agents. These drugs are Food and Drug Administration–approved for purposes other than brain injuries; however, preclinical and clinical studies have shown their efficacy in ameliorating the various detrimental outcomes of TBI.